169k views
3 votes
Find the equation of the inverse.
y = {2}^(x + 5) - 6

User Keshan
by
6.2k points

1 Answer

1 vote

Find the equation of the inverse.


y = {2}^(x + 5) - 6

we have


y=\mleft\{2\mright\}^{\mleft\{x+5\mright\}}-6

step 1

Exchange the variables

x for y and y for x


x=\{2\}^{\{y+5\}}-6

step 2

Isolate the variable y


(x+6)=2^((y+5))

apply log both sides


\begin{gathered} \log (x+6)=(y+5)\cdot\log (2) \\ y+5=(\log (x+6))/(\log (2)) \\ \\ y=(\log(x+6))/(\log(2))-5 \end{gathered}

step 3

Let


f^((-1))(x)=y

therefore

the inverse function is


f^((-1))(x)=(\log(x+6))/(\log(2))-5

User Ragu Natarajan
by
5.5k points